Efficacy and safety of calcineurin inhibitors (CNIs) for septic patients in ICU: a cohort study from MIMIC database - Miao, ShengHui; Yang, Mingkun; Li, Wen; Yang, Zhouxin; Yan, Jing (Frontiers in Pharmacology, 2024)
Background: Sepsis is marked by a dysregulated immune response to infection. Calcineurin inhibitors (CNIs), commonly used as immunosuppressants, have unique properties that may help mitigate the overactive immune response in sepsis, potentially leading to better patient outcomes. This study aims to assess whether CNIs improve prognosis in septic patients and to evaluate any associated adverse reactions. Methods: We utilized the Medical Information Mart for Intensive Care IV 2.2 (MIMIC-IV 2.2) database to identify septic patients who were treated with CNIs and those who were not. Propensity score matching (PSM) was employed to balance baseline characteristics between the CNI user group and the non-user group. The primary outcome was 28-day mortality, analyzed using the Kaplan-Meier method and Cox proportional hazard regression models to examine the relationship between CNI use and patient survival. Results: From the MIMIC-IV database, 22,517 septic patients were identified. After propensity score matching, a sample of 874 patients was analyzed. The CNI group exhibited a significantly lower 28-day mortality risk compared to the non-user group (HR: 0.26; 95% CI: 0.17, 0.41) in the univariate Cox hazard analysis. Kaplan-Meier survival curves also demonstrated a significantly higher 28- and 365-day survival rate for CNI users compared to non-users (log-rank test p-value = 0.001). No significant association was found between CNI use and an increased risk of new-onset infection (p = 0.144), but an association with mild hypertension (P < 0.001) and liver injury (P < 0.001) was observed. Conclusion: The use of calcineurin inhibitors was associated with reduced short- and long-term mortality in septic patients without an increased incidence of new-onset infections, hyperkalemia, severe hypertension, or acute kidney injury (AKI). However, CNI use may lead to adverse effects, such as liver injury and mild hypertension.